2012
DOI: 10.1002/eji.201142148
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3‐independent loss of regulatory CD4+T‐cell suppressive capacities induced by self‐deprivation

Abstract: In the periphery, Foxp3 expression is considered sufficient to maintain natural regulatory CD4 + T-cell suppressive function. In this study, we challenge this model. Indeed, in mouse chimeras in which major histocompatibility complex (MHC) class II expression is restricted to the thymus, peripheral regulatory CD4 + T cells lack suppressive activity. In addition, regulatory CD4 + T cells recovered 5 days after transfer into recipient mice lacking expression of MHC class II molecules (self-deprived) are unable t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Purified Ly-6C À or Ly-6C þ CD4 T N cells were stimulated for 3 days with coated anti-CD3 and anti-CD28 Abs in the presence of 1 ng ml À 1 of TGFb1 and then let to rest for 3 more days in the presence of recombinant human IL-2 (13 ng ml À 1 ; R&D). GFP-expressing cells were then sorted using flow cytometry, and the suppressive capacities of these highly purified Foxp3-expressing cells were then assessed as previously described 31 . Briefly, conventional CD4 T cells (GFP À CD4 þ T cells) were purified from LNs of C57BL/6 Foxp3-GFP mice, labelled with Cell Trace Violet (Invitrogen) and stimulated for 64 h, alone or together with Treg cells at various Treg/Tconv-cell ratios.…”
Section: Methodsmentioning
confidence: 99%
“…Purified Ly-6C À or Ly-6C þ CD4 T N cells were stimulated for 3 days with coated anti-CD3 and anti-CD28 Abs in the presence of 1 ng ml À 1 of TGFb1 and then let to rest for 3 more days in the presence of recombinant human IL-2 (13 ng ml À 1 ; R&D). GFP-expressing cells were then sorted using flow cytometry, and the suppressive capacities of these highly purified Foxp3-expressing cells were then assessed as previously described 31 . Briefly, conventional CD4 T cells (GFP À CD4 þ T cells) were purified from LNs of C57BL/6 Foxp3-GFP mice, labelled with Cell Trace Violet (Invitrogen) and stimulated for 64 h, alone or together with Treg cells at various Treg/Tconv-cell ratios.…”
Section: Methodsmentioning
confidence: 99%
“…C57BL/6 CD3ε 2/2 mice (26) were crossed with MHC II D/D mice (27) to obtain CD3ε/MHC II double-deficient mice (CD3ε 2/2 II D/D mice) (13). C57BL/6 Foxp3-GFP reporter mice were initially provided by Dr. Bernard Malissen (Centre d'Immunologie de Marseille-Luminy, Marseille, France) (28,29) and maintained in our own animal facilities. Experiments were carried out in accordance with the guidelines of the French Veterinary Department.…”
Section: Methodsmentioning
confidence: 99%
“…By comparing the other subsets to naive and memory CD8 + a/b T cells, we found that the CD27 + g/d T cell compartment include naive-like and memorylike lymphocytes that share many phenotypic, functional, and homeostatic characteristics with their adaptive a/b T cell counterparts. (18) were maintained in our own animal facilities, under specific pathogen-free conditions. C57BL/6 Foxp3-GFP CD45.2 mice were initially obtained from Dr. Bernard Malissen (Centre d'Immunologie de Marseille-Luminy, France) (19).…”
Section: Cd44mentioning
confidence: 99%
“…GFPexpressing cells were then flow cytometry sorted, and the suppressive capacities of these highly purified Foxp3-expressing cells were then assessed as previously described (18). Briefly, conventional CD4 T cells (GFP 2 CD4 + T cells) were purified from LNs of C57BL/6 CD45.2 Foxp3-GFP mice, labeled with Cell Trace Violet (Invitrogen), and stimulated for 64 h, alone or together with Tregs at various Treg/conventional T cell ratios.…”
Section: In Vitro Polarization Assaysmentioning
confidence: 99%